Fear of pain as a predictor of concurrent and downstream PTSD symptoms. (August 2021) - Barbano, Anna C.; Tull, Matthew T.; Christ, Nicole M.; Xie, Hong; Kaminski, Brian; Wang, Xin
Highlights: Examined role of pain anxiety dimensions in concurrent and later PTSD symptoms. Pain anxiety dimensions assessed 3-months post-traumatic exposure. PTSD assessed 3- and 12-months post-traumatic exposure. Physiological reactivity and fear of pain predicted concurrent PTSD symptoms. Fear of pain prospectively associated with PTSD symptoms at 12-months. Abstract: Background: Pain anxiety has been associated with more severe posttraumatic stress disorder (PTSD) symptoms. However, the unique role of individual domains of pain anxiety has yet to be explored in the prediction of PTSD severity. This study examined whether specific pain anxiety domains (i.e., cognitive anxiety, escape/avoidance, fear of pain, and physiological anxiety) predict both concurrent and downstream PTSD symptoms above and beyond other PTSD risk factors. Method: Participants were 63 survivors of traumatic events with moderate to high baseline pain treated in the emergency department and assessed for PTSD symptoms and pain anxiety at 3- and 12-months. Results: Three-month pain anxiety domains of fear of pain and physiological anxiety (inversely related) significantly predicted concurrent 3-month PTSD symptoms above and beyond other established PTSD risk factors (i.e., sex, age, pain, and trauma type). However, only 3-month fear of pain significantly predicted 12-month PTSD symptoms. Conclusions: Findings highlight the relevance of specific pain anxiety domains in concurrent and future PTSD symptoms and suggest the importance of evaluating pain anxiety among patients with PTSD. Interventions focused on increasing willingness to experience and tolerate fear of pain may help mitigate this risk, thereby improving outcomes for individuals with acute PTSD symptoms.